2015
DOI: 10.20473/j.djmkg.v48.i1.p26-30
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nanochitosan hydrogel membrane on absorbtion of nickel, inhibition of Streptococcus mutans and Candida albicans

Abstract: Background: The use of fixed orthodontic appliance for a long time can potentially cause nickel ion release, increase in the growth of Streptococcus mutans (S. mutans) and Candida albicans (C. albicans). Chitosan has the ability to bind metal, antibacterial and antifungal. Physical modification of chitosan into the nanoparticles size will expand the surface of the chitosan so that the absorption of nickel ions and the inhibition of growth bacteria and fungi can be increased. Purpose: The purpose of the study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…A number of scientists have proved that metal and metal-derived nanoparticles stand as strong antifungal agent (Chen et al, 2016). Research by Triawan et al, 2015 revealed that when spores of R. stolonifer are treated with magnesium oxide and zinc oxide nanoparticles, the viability of the spores and their propagation is completely inhibited. In order to completely triggered the propagation of a phytopathogen, it is important to trigger its propagative unit i.e., spore (Judelson and Blanco, 2005).…”
Section: Spore Viability Assaymentioning
confidence: 99%
“…A number of scientists have proved that metal and metal-derived nanoparticles stand as strong antifungal agent (Chen et al, 2016). Research by Triawan et al, 2015 revealed that when spores of R. stolonifer are treated with magnesium oxide and zinc oxide nanoparticles, the viability of the spores and their propagation is completely inhibited. In order to completely triggered the propagation of a phytopathogen, it is important to trigger its propagative unit i.e., spore (Judelson and Blanco, 2005).…”
Section: Spore Viability Assaymentioning
confidence: 99%